Beyond acute infection: molecular mechanisms underpinning cardiovascular complications in long COVID - Mostafa, Roba Hamed; Moustafa, Ahmed (Frontiers in Cardiovascular Medicine, 2024)
SARS-CoV-2, responsible for the global COVID-19 pandemic, has manifested significant cardiovascular implications for the infected population. These cardiovascular repercussions not only linger beyond the initial phase of illness but have also been observed in individuals who remain asymptomatic. This extended and pervasive impact is often called the post-acute COVID-19 syndrome (PACS) or "Long COVID". With the number of confirmed global cases approaching an alarming 756 million, the multifaceted challenges of Long COVID are undeniable. These challenges span from individual health complications to considerable burdens on worldwide healthcare systems. Our review comprehensively examines the complications of the persistent cardiovascular complications associated with COVID-19.Furthermore, we shed light on emerging therapeutic strategies that promise to manage and possibly mitigate these complications. We also introduce and discuss the profound concerns regarding the potential transgenerational repercussions of SARS-CoV-2, emphasizing the need for a proactive and informed approach to future research and clinical practice.